Accruals quality, underwriter reputation, and corporate bond underpricing: Evidence from China - Si Xu; Gong Guangming; Xun Gong (China Journal of Accounting Research, 2017)
This study examines the relationship between accruals quality and the underpricing of corporate bonds in China and how underwriter reputation affects this relationship. We find that (1) accruals quality is negatively associated with the magnitude of bond underpricing and (2) the impact of low accruals quality on underpricing is partially offset by hiring reputable underwriters. A path analysis shows that approximately 11% of the effect of accruals quality on underpricing is attributable to the indirect path through reputable underwriters, suggesting that accruals quality is more effective than reputable underwriters in lowering bond underpricing. These findings are significant for initial bond offerings, but not for secondary bond offerings. We also find that low accruals quality is associated with more restrictive non-price contract terms such as greater collateral requirements and stricter covenants.
Keywords: G10; M41; 650; Bond underpricing; Accruals quality; Reputable underwriters; Information asymmetry